PENGAWASAN KOMISI PENYIARAN INDONESIA DAERAH RIAU TERHADAP PENYELENGGARAAN PENYIARAN TV KABEL DI PEKANBARU TAHUN 2015-2016 - Satria Sambodo; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The development of the broadcasting world in Indonesia, especially television, has become the attention of many circles. Many opinions of people who say that the world of television in Indonesia has forgotten the moral side, culture, and ethics of this nation. If in the rules of the Indonesian Broadcasting Commission it violates the Broadcast Program Standards (SPS). Indonesian Broadcasting Commission (KPI) is an independent state institution established through Law no. 32 of 2002 On broadcasting with the aim of organizing all matters concerning broadcasting in Indonesia. This Independent Institution consists of central KPI and KPID in areas whose duties are coordinative, national policy is determined by KPI and while the extension at the provincial level becomes the coverage of KPID.This research is descriptive by using qualitative approach that is research which exposes and explains problem to object which will be meticulously, research method is case study method because focus of research lies in phenomenon in real life. This study uses the theory of supervision, qualitative research methods descriptive this be an option in this study because the author wants to examine more deeply how KPID supervision of cable TV broadcasting in Pekanbaru by looking at the phenomenon or reality that occurred in the field. Based on the results of analysis of this study shows that in the supervision of broadcasting cable TV broadcasting is done directly by KPI and KPID as an institution that stands independently and has prerogative rights to revoke the broadcasting license if found irregularities, and the role of society is also emphasized because the community is asked as an extension of supervision and Not only serve as consumers only, the purpose of this is in order to get penyirenggaranya good and healthy penyiran in society.Keywords :Controling, Cable Television Broadcasting